Application of critical thinking strategies to develop inferential reading skills in students of 1 baccalaureate in unidad educativa José Benito Benítez San Andrés during the school year 2017-2018 st - Avilés Torres, Nicole Katrina (2018)
The purpose of this research is to improve inferential reading skills through the application of different kinds of critical thinking strategies because mechanical, repetitive and lacking of reflection learning is a problem that students and teachers face nowadays. The first phase of the project involves previous analysis of the reading situation to evaluate the influence of critical thinking strategies on the inferential reading abilities of 1st baccalaureate students at Unidad Educativa Jose Benito Benitez San Andres during the school year 2017-2018……..